2012
DOI: 10.5897/jahr11.062
|View full text |Cite
|
Sign up to set email alerts
|

HIV-Related knowledge, attitudes, and practice among educated young adults in Botswana

Abstract: Students at the University of Botswana, an at-risk group, have previously been shown to have high levels of risky sexual behavior despite widespread knowledge that these behaviors might lead to HIV-1 infection. As there have recently been considerable efforts focused on HIV-1 prevention in Botswana through nationwide media education campaigns and the opening of voluntary counselling and testing centers, re-evaluation of HIV-related knowledge, attitudes, and practices among students is needed. A cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Similar barriers to use of condoms were found in another study of Botswana youth: decreased pleasure, the influence of drugs and alcohol, trust of one’s partner, unavailability of condoms, influence of peers, unprotected sex as proof of love, desire for money and gifts. 23 A study conducted in South Africa also identified the difficulties that families have in openly discussing issues of sex and HIV. 24 …”
Section: Discussionmentioning
confidence: 99%
“…Similar barriers to use of condoms were found in another study of Botswana youth: decreased pleasure, the influence of drugs and alcohol, trust of one’s partner, unavailability of condoms, influence of peers, unprotected sex as proof of love, desire for money and gifts. 23 A study conducted in South Africa also identified the difficulties that families have in openly discussing issues of sex and HIV. 24 …”
Section: Discussionmentioning
confidence: 99%
“…In Botswana, for example, a study conducted previously showed that half of the students could be perceived to be at risk of HIV, while the same participants thought that each sexually active student should be aware of his HIV status through regular testing. 22…”
Section: Introductionmentioning
confidence: 99%
“…Young people, particularly females aged 15-24 years, are reported to be most at risk; existing research suggests that high levels of risky sexual behavior are the major contributor to high STI infections in the region. [5][6][7] . Risky sexual behavior has been defined as having sexual intercourse with at least one non-spousal partner without using a barrier method 8 .…”
Section: Introductionmentioning
confidence: 99%